Model of vertical crystal growth of Cd(1-x)ZnxTe single-crystals - L. A. Gvelesiani (Тонкие химические технологии, 2010)
The growth process and properties of CdZnTe single crystals of solid solutions was considered. A mathematical model of the process was built taking into account radiative heat transfer. An analytic form for calculating the view factor in different geometric configurations with axial symmetry was obtained.